4CPS-132 Level of evidence and degree of recommendation of intravenous immunoglobulin in auto-immune neurological diseases. (2nd March 2018) - Serramontmany, E; Alonso, C; Gámez, J; Salvadó, M; Perez, MT; Alvarez, A; Perez, JL; Betriu, L; Montoro, B
Abstract : Background: Intravenous immunoglobulin (IVIG) is being increasingly used to treat neuroimmunological diseases. Randomised clinical trials (RCT) have proved its efficacy in certain indications, but evidence is scarce in others. Purpose: Evaluate the prevalence, level of evidence and degree of recommendation of IVIG in different neuroimmunological indications. Material and methods: Ambispective observational study involving three tertiary hospitals including patients diagnosed with neuroimmunological diseases chronically receiving IVIG. Sex, age and main diagnosis were recorded for each patient. Demographic and clinical data were collected from electronic medical record and pharmacy dispensing software. The adequacy analysis (degree of evidence and recommendation) was contrasted against the British National Health System Clinical Guide for the use of IVIG. For indications with insufficient evidence, further research was performed. Results: One hundred and seventeen patients were included (51 females) with a median age of 53 (18–85). Most were diagnosed with chronic inflammatory demyelinating polyradiculoneuropathy, CIDP (45); followed by myasthenia gravis, MG (25); multifocal motor neuropathy, MMN (12); lower motorneuron, LMN (4); Guillain–Barre syndrome, SGB (5), stiff person syndrome (3), CIDP-like neuropathy (3), Eaton–Lambert syndrome, LEMS (3); Bickerstaff encephalitis, EB (3); inclusion body myositis, IBM (2); amyotrophic lateral sclerosis, ALS (2); anti-GAD +paraneoplastic syndrome (2); polymyositis (2); autoimmune epilepsy (1); transverse myelitis (1); Kabuki syndrome (1); Kinsbourne syndrome (1); Sjögren syndrome (1); and idiopathic lumbosacral plexopathy, PLSI (1). There is a high level of evidence (A, Ia) and degree of recommendation for the use of IVIG in CIDP, SGB, CIDP-like-neuropathy and MMN (55.5%). In stiff person syndrome and LEMS, however, the degree of recommendation is lower due to the absence of meta-analysis (A, Ib) (5.12%). For LMN, EB, anti-GAD +paraneoplastic syndrome, myelitis, polymyositis, epilepsy, Kabuki syndrome, Kinsbourne Syndrome and Sjögren syndrome there are not high-quality RCT, so the degree of recommendation and evidence are low (C, III) (13.6%). There are not recommendations for using IVIG in PLSI and ALS (D, IV) (2.5%). Conclusion: In neuroimmunological diseases, IVIG are used for indications with a high level of evidence (I-II) and degree of recommendation (A-B). However, 16% of indications with low evidence (III-IV) and recommendation (C-D) were recorded. Pharmacy services must guarantee the correct use of IGIV. References and/or Acknowledgements: Thanks to all authors for their contributions No conflict of interest